2006
DOI: 10.1007/s10533-006-9015-9
|View full text |Cite
|
Sign up to set email alerts
|

Regional Assessment of N Saturation using Foliar and Root $$\varvec {\delta}^{\bf 15}{\bf N}$$

Abstract: N saturation induced by atmospheric N deposition can have serious consequences for forest health in many regions. In order to evaluate whether foliar d 15 N may be a robust, regional-scale measure of the onset of N saturation in forest ecosystems, we assembled a large dataset on atmospheric N deposition, foliar and root d 15 N and N concentration, soil C:N, mineralization and nitrification. The dataset included sites in northeastern North America, Colorado, Alaska, southern Chile and Europe. Local drivers of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
190
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(220 citation statements)
references
References 85 publications
17
190
8
Order By: Relevance
“…Species differences in foliar d 15 N values have been reported in the northeastern US (Nadelhoffer et al, 1999;Templer, 2001;Pardo et al, 2006;Pardo et al, 2007). These differences in foliar d…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Species differences in foliar d 15 N values have been reported in the northeastern US (Nadelhoffer et al, 1999;Templer, 2001;Pardo et al, 2006;Pardo et al, 2007). These differences in foliar d…”
Section: Discussionmentioning
confidence: 86%
“…15 N values are typically more closely linked to measures of soil N cycling than are foliar %N measurements, they may be a better early indicator of N saturation than foliar %N alone (Pardo et al, 2006). Combining measurements of foliar d 15 N and %N may provide the best information about N cycling dynamics at a given site, particularly for regional surveys.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these regional-to global-scale changes, many forests are experiencing local changes in fire regimes, drought, and the introduction of non-native plants and animals while recovering from earlier logging and windthrow. Not only do many of these factors have the potential to interact in their effects on forest processes, but they also have the potential to enhance or dampen N availability, which often limits primary productivity and influences forest species composition (Pepper et al, 2007). For example, experiments have suggested that elevated CO 2 may decrease terrestrial N availability (Johnson, 2006;Luo et al, 2004), while chronic N deposition may increase N availability to temperate forests (Aber et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many processes that discriminate against 15 N, stand-level plant δ 15 N generally increases with increasing N availability, here defined as the supply of N to terrestrial plants and soil microorganisms relative to their N demands (Schimel and Bennett, 2004). In forests, high δ 15 N values are found in soils and leaves of ecosystems with high rates of nitrification (Pardo et al, 2006), high rates of denitrification (Houlton et al, 2006), partial nitrification followed by nitrate leaching (Pardo et al, 2002), and low reliance on mycorrhizal fungi for plant N uptake (Hobbie and Colpaert, 2003;Högberg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystems with high N availability, such as those that are fertilized with N, exhibit high values of natural abundance 15 N: 14 N ratios (␦ 15 N) in leaf tissue and soil (18). As with tree leaves (19), enrichment of wood with 15 N occurs with high N availability, and therefore dendroisotopic records have been used to reconstruct past N availability (20,21).…”
mentioning
confidence: 99%